2016
DOI: 10.1186/s12872-016-0334-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HeartWare ventricular assist device on the von Willebrand factor: results of an academic Belgian center

Abstract: BackgroundLeft Ventricular Assist Device (LVAD) is a promising therapy for patients with advanced heart failure (HF), but bleeding complications remain an important issue. Previous series show that acquired von Willebrand syndrome was present in up to 100 % of first generation LVAD recipients. We report the effects of new generation LVADs on vW factor (vWF) metabolism and activity in our center.MethodsFifteen LVAD recipients (HeartWare®, Framingham, MA, USA) were compared to 12 HF patients, matched for age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…Varying levels of shear stress in the CentriMag, HMII and HVAD could explain different collagen binding activity between devices. This observation is consistent with previous findings revealing that HMII and HVAD patients have similarly reduced vWF multimers and vWF activity, which might explain gastrointestinal bleeding episodes in HMII treated patients (17,41). Notably, the HMII device generates higher levels of shear stress than the newer HeartMate 3 (HM3; Abbott, Thoratec, Pleasanton, CA, US) device.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Varying levels of shear stress in the CentriMag, HMII and HVAD could explain different collagen binding activity between devices. This observation is consistent with previous findings revealing that HMII and HVAD patients have similarly reduced vWF multimers and vWF activity, which might explain gastrointestinal bleeding episodes in HMII treated patients (17,41). Notably, the HMII device generates higher levels of shear stress than the newer HeartMate 3 (HM3; Abbott, Thoratec, Pleasanton, CA, US) device.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the enhanced vWF degradation profile and decreased CBA observed in HMII and HVAD patients (41,47). Thus our more extensive in vitro results could relate to the prominence of thrombosis and bleeding identified in HMII and HVAD patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, these slight differences are unlikely to be clinically significant, as reported in studies performed in patients undergoing coronary artery bypass [ 46 ]. Moreover, in patients with centrifugal devices, the vWF antigen and vWF activity did not differ among individuals with blood group “O” compared to the other blood groups [ 47 ].…”
Section: Pathophysiology Of Thrombosis and Bleeding In Lvad Patientsmentioning
confidence: 99%
“…However, information concerning the changes in VWF parameters on long-term support (> 4 months to years after LVAD implant) and after heart transplantation is scarce [2]. In addition, only a few studies describe ADAMTS13 parameters after LVAD implantation and found either normal or decreased ADAMTS13 activities [6][7][8]. Hence, the aim of this study was a long-term follow up of VWF (VWF multimer size, antigen and activity) and ADAMTS13 (ADAMTS13 antigen and activity) parameters in LVAD patients and in those patients undergoing heart transplantation.…”
mentioning
confidence: 99%